Genome-wide association studies in the Japanese population identify seven novel loci for type 2 diabetes - Minako Imamura (Nature Portfolio, 2016)
Here, Imamuraet al. conduct meta-analysis of genome-wide association studies to identify novel susceptibility loci for type 2 diabetes (T2D) in the Japanese population. By doing so, this study shows that both ethnicity-specific and ethnically-shared genetic loci can contribute to T2D risk.